Preliminary investigation of digital reading techniques and their impact on eye movement and blinking rate / Ai-Hong Chen ... [et al.] - Chen, Ai-Hong; Rosli, Saiful Azlan; Mohd Zain, Nurfatina Aqilah; Mokhtar, Siti Nuraiman; Teoh, Swee-Chai (Faculty of Health Sciences, Universiti Teknologi MARA, 2023)
This preliminary study investigates the effect of four digital reading techniques on eye movement and blinking rate. A total of ten young adults (aged 18-26 years) were recruited in this preliminary investigation about the ocular impact of digital reading techniques. The inclusion criteria were bestcorrected visual acuity of 6/6 and N5 (6/9 Snellen equivalent) or better for far and near, respectively. The exclusion criteria were any known vision problems and ocular diseases. Four types of digital reading techniques were studied: (1) skimming, (2) scanning, (3) intensive reading and (4) extensive reading. The ocular parameters encompass eye movements (fixation and saccadic) and blinking rate. The measurements were recorded using a Dikablis TM eye tracker. There was no significant difference among the four types of digital reading techniques in all eye movement investigations (p>0.05). However, the blinking rate was the lowest during 'scanning technique' (average of 10.90 blinks per minute) and the highest during 'extensive reading' (average of 26.95 blinks per minute) (Friedman ANOVA Test =11.35, p=0.03). The eye movement patterns remain the same regardless of the types of digital reading techniques may indicate the robustness of individual visual search capability. The significant variation in blinking rate might be associated with the cognitive demand of the reading techniques. It will be interesting to investigate the ocular impact of these different digital reading techniques among school children due to the digital shift in our education system.